Causes of increased concentration of fluorides in groundwater in Srebrenica municipality - Boban Jolović; Andrijana Stevanović; Maja Nogić (Journal of Engineering & Processing Management, 2017)
Groundwater, as the mainresource of drinking water in the Republic of Srpska, is sometimes neglected regarding quality monitoring. It is especiallya characteristic of rural water supply sources as autonomous waterworks, individual intakes and wells. For the first time comprehensive analyses of the groundwater quality in rural areas of Srebrenica municipality have been provided in 2010. The results are more than interesting. Beside some standard problems in physic-chemical properties like increased turbidity, iron and manganese, there was emerged problem of increased fluoride concentration in more than one third samples of groundwater. The study of fluoride concentration, given in this paper, includes the causes of this phenomena and possible health impacts. It defines geological setting, or precisely mineralogical properties of the rocks and their interaction with groundwater, as a key factor of the problem. Further, analyses include recommendations regarding future exploration areas with probably same effect of the geological setting on groundwater quality in the territory of the Republic of Srpska. It is very important because the problems related to the long-term consumption of groundwater with fluoride concentration above 1.2 mg/L could be a trigger for very serious diseases like dental and skeletal fluorosis, diseases of pineal gland, kidneys, urinary bladder, thyroid gland, gastro-intestinal tract etc.
Keywords: concentration; drinking water fluoride; geology; health; Srebrenica